Cardiac Shock Wave Therapy Ameliorates Myocardial Ischemia in Patients With Chronic Refractory Angina Pectoris: A Randomized Trial - Weijing, Liu; Ximin, Fan; Jianying, Shen; Mengyun, Zhu; Xuehua, Fan; Yawei, Xu; Liqiong, Hong (Frontiers in Cardiovascular Medicine, 2021)
This study aimed to evaluate the safety and efficiency of cardiac shock wave therapy (CSWT) in the treatment of refractory angina through analysing a total of 87 patients with chronic refractory angina pectoris. CSWT was well tolerated in all patients with no procedural complications or adverse effects. CSWT significantly improved symptoms as evaluated by Canadian Cardiovascular Society (CCS) class sores, Seattle angina questions (SAQ) and 6-min walk test (p<0.05). Imaging results through dynamic single photon emission computed tomography (D-SPECT examinations) showed the ischemia region of myocardia was also reduced. However, no significant changes could be observed in the control group. In summary, CSWT is safe and effective. It contributes to improving myocardial perfusion and reducing clinical angina symptoms without affecting global myocardial perfusion.